Rotating Goblet and Talking Profiles: Does a Rotating Goblet Increase the Figural Dominance of Profiles in Rubin's Type of Figure-Ground Reversal Patterns?. (October 2014) - Wake, Hiromi; Wake, Tenji; Oyama, Tadasu
We present a novel three-dimensional (3-D) version of Rubin's classical bistable goblet–profiles figure. An actual goblet sculpture was produced and rotated on a turntable in front of a white background. As the goblet rotates about its central axis, small circular asymmetries around the lips and chin region give a clear impression of two white profiles talking to each other. Although the profiles actually correspond to empty space or white background, they are more likely to be perceived as 'figure' than the 3-D goblet itself. Four experiments that presented the actual goblet (experiment 1) or two-dimensional (2-D) movies of it (experiments 2–4) were designed to verify these observations. We measured perceptual dominance of profiles as 'figure' and rate of reversal as a function of three factors: Motion (static vs rotating), orientation (upright vs inverted), and configuration (face-to-face vs back-to-back). Results for the rotating goblet showed a statistically reliable preference for perceiving the talking profiles as 'figure'. Deforming the profiles by manipulating the vertex angle of the mouth region produced an inverted U-shaped curve with the peak representing the stimulus condition in which the profiles perception was most remarkable. We discussed a number of 3-D and 2-D figure-ground factors that might apply to this rather complex stimulus situation.